اللغة العربية من الأصالة إلى تحديات العولمة - لعبيدي, منيرة (جامعة الوادي - University of Eloued, 2021)
تعدّ اللّغة العربيّة من أهم مقوّمات الأمّة الإسلاميّة، فهي عنوان هويّة الإنسان العربيّ المسلم، وصوته المعبّر عن فكره، ووجدانه، وعقيدته، وثقافته، وتراثه. واليوم، تواجه اللّغة العربيّة مخاطر عديدة باتت تهدّد استقرارها داخليّا وخارجيّا، بما يحاك ضدّها من مؤامرات خبيثة، تريد زعزعة مكانتها بين أبنائها وأحبّائها من المسلمين، بزرع الشّك في قدرتها على مواكبة التّطورات العلميّة في ظلّ وجود عدوّ شرس اسمه "العولمة" الّذي يسعى لفرض قانون هيمنة اللّغة الواحدة على العالم في مقابل القضاء على اللّغات الأخرى. وقد جاءت هذه الدّراسة لتكشف عن منزلة اللّغة العربيّة بين اللّغات قديما وحديثا، مع التّركيز على معرفة المخاطر الّتي تواجهها حديثا، وسبل مواجهتها للارتقاء بها والمحافظة عليها. The Arabic language is one of the most important components of the Islamic nation. It is the title of the identity of the Arab Muslim man, his voice, expressing his thoughts, conscience, creed, culture and heritage. Today, the Arabic language faces many dangers that threaten its stability, domestically and abroad, with malicious plots to undermine it, which seek to undermine its position among its Muslim sons and loved ones, by casting doubt on its ability to keep up with scientific developments in light of the existence of a fierce enemy called "globalization" which seeks to impose the rule of one language on the world in exchange for eliminating other languages. The study revealed the status of the Arabic language among languages, both old and new, with a focus on knowing the dangers it is facing recently and the ways to confront them in order to improve and preserve them.
مقال
Keywords: اللغة العربية ; العولمة ; التحديات ; الهوية ; السيادة